MAKNA KUBAH MASJID DI PULAU JAWA STUDI KASUS: MASJID AGUNG DI JAWA - Shabrina Hasnadhiya Retnoasih; Satriya Wahyu Firmandhani (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2017)
bstract:.Mosque is a house of worship of Muslims and is a work of art and culture of architecture. The development of Islam is in line with the development of architecture, namely Mosque Architecture. As we often see today, the mosque is identical to the dome on its roof. In its use, the dome of the mosque is used as a structure and construction but some are only used as aesthetic ornaments. With the many uses of the dome on the building of the mosque, making some people think the dome that is used as a hallmark of this mosque is the ornament of the Islamic Architects. If noticed, the ancient mosque on the island of Java at first has no dome. Characteristic of the ancient mosque in Java, among others, the roof is in the form of overlapping two to five levels upwards. While the mosque building that we often encounter today is a mosque that has a dome roof. We need to learn more about the development of this mosque architecture in the context of roof overlap and domes. So we need to know whether the meaning of the dome applied to the mosque in Java. This study reveals that, the meaning of the dome evolved according to the needs of the mosque itself, such as political symbols, gratitude, and media of da'wah. Keyword: mosque, dome, meaning Abstrak: Masjid adalah rumah ibadah umat Islam dan merupakan suatu karya seni dan budaya dalam bidang arsitektur. Perkembangan Agama Islam sejalan dengan perkembangan arsitekturnya, yakni Arsitektur Masjid. Seperti yang sering kita lihat sekarang, Masjid sangat identik dengan kubah di bagian atapnya. Dalam penggunaannya, kubah masjid ada yang digunakan sebagai struktur dan konstruksi namun ada pula yang hanya digunakan sebagai ornamen estetika. Dengan banyaknya penggunaan kubah pada bangunan masjid, menjadikan sebagian orang beranggapan kubah yang dijadikan ciri khas masjid ini adalah ornamen dari Arsitekur Islam. Jika diperhatikan, masjid kuno di pulau Jawa pada awalnya tidak ada yang memiliki kubah. Ciri khas masjid kuno di Jawa antara lain atapnya yang berbentuk tumpang bersusun dua hingga lima tingkat keatas semakin mengecil. Sedangkan bangunan masjid yang sering kita temui saat ini adalah masjid yang memiliki atap kubah. Perkembangan arsitektur masjid ini dalam konteks atap tumpang dan kubah, perlu kita pelajari lebih lanjut. Sehingga perlu kita ketahui apakah makna kubah yang diterapkan pada masjid di Jawa. Penelitian ini mengungkap bahwa, pemaknaan kubah berkembang sesuai kebutuhan yang di capai masjid itu sendiri, seperti simbol politik, rasa syukur,dan media dakwah. Kata kunci: masjid, atap kubah, makna